RANCANG BANGUN APLIKASI PERENCANAAN BAHAN BAKU MENGGUNAKAN METODE MATERIAL REQUIREMENT PLANNING PADA PT MULTI KADERA SEJATI - Kurniawan, Muhammad risqi; Supriyanto, Antok; Arrosyidi, Achmad (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT Multi Kadera Sejati is a manufacturing company located at Jl Tropodo, Krian. Sidoarjo RT06 RW03. The company is engaged in manufacturing producing various wicker chairs. The company is engaged in manufacturing producing various wicker chairs. Of all the types of seats almost all products for export. There are several problems, namely, the PPIC officer to make raw material procurement based on intuition / estimate only so that there are often shortages and excess of raw materials, if the shortage resulted in slowing down the production process, resulting in inappropriate delivery time targets to customers, and if the excess will have high impact storage costs and risk of loss and damage to raw materials. And for information from the warehouse provided PPIC. So with the way the information is delivered less quickly, and PPIC late in ordering materials to cover the existing shortages in the warehouse. Based on the availability of raw material stock and problems related to data warehouse data updating and data consistency can be solved by MRP method in the form of web-based computer application. Expectations of the use of these applications is an increase in effectiveness and efficiency, and timeliness in delivery to consumers can be met that led to increased profits of the company. This journal discusses the planning of raw materials for production in PT Multi Kadera Sejat